Monitoramento ambiental em uma escola da cidade de São Carlos - SP: ênfase em qualidade do ar interior - Comin, Tatiane Tagino (2012)
Over the last decades, a great deal of research has been conducted to find out more about indoor air quality (IAQ) problems and likewise there are some studies designed to measure environmental conditions linking health problems and students and teachers performance to poor indoor air quality in classroom settings. Given the overwhelming magnitude of this issue, the purpose of this work was to carry out an environmental monitoring study with a focus on indoor air quality in a public school, Dr. Álvaro Guião, located in the downtown area of São Carlos with high traffic volumes. The following parameters were measured in order to calculate their values: total particulate matter (TPM) and inhalable particles (PM2,5 and PM10), air temperature, relative humidity, carbon dioxide (CO2), noise. In addition, the chemical characterization of the particulate matter collected by X-Ray Fluorescence (XRF) technique was accomplished. With respect to the mean concentrations of CO2, PM2,5 and PM10, the results showed that the applicable regulatory requirements have been met in accordance with the National Regulatory Agency for Sanitary Vigilance (ANVISA) and World Health Organization (WHO) guidelines, respectively, while two different measurements of TPM mean concentrations were significantly higher than the levels recommended by the Brazilian Association of Refrigeration, Air Conditioning, Ventilation, and Heat (ABRAVA). PM analysis using XRF method was utilized to identify the following elements: Ca, Cu, Fe, K, S, Si, and Ti, from external sources such as vehicle emissions, re-suspension of soil and sugarcane burning, and internal sources as the traditional chalk (which contains calcium compounds) used by the teachers. Both temperature and humidity readings have exceeded several times the levels required by ANVISA, however, a thermal discomfort was observed only in three different days, whereas the noise levels measured during the sample period extrapolated the satisfactory levels recommended by the Brazilian Technical Standards Association (ABNT). All monitored parameters both inside and outside the classrooms exhibited higher indoor levels with I/O ratio (ratio of mean concentrations indoors and outdoors) a few times greater than 1 and measured values between the cross-correlation coefficients showed that most of the parameters were negatively correlated with rainfall, showing that there is a close relationship between high pollution levels and lower rainfall.